The storytelling animal eaudiobook How stories make us human. - Gottschall, Jonathan (Tantor Media, 2012)
Humans live in landscapes of make-believe. We spin fantasies. We devour novels, films, and plays. Even sporting events and criminal trials unfold as narratives. Yet the world of story has long remained an undiscovered and unmapped country. It's easy to say that humans are "wired" for story, but why? In this delightful and original book, Jonathan Gottschall offers the first unified theory of storytelling. He argues that stories help us navigate life's complex social problems—just as flight simulators prepare pilots for difficult situations. Storytelling has evolved, like other behaviors, to ensure our survival. Drawing on the latest research in neuroscience, psychology, and evolutionary biology, Gottschall tells us what it means to be a storytelling animal. Did you know that the more absorbed you are in a story, the more it changes your behavior? That all children act out the same kinds of stories, whether they grow up in a slum or a suburb? That people who read more fiction are more empathetic? Of course, our story instinct has a darker side. It makes us vulnerable to conspiracy theories, advertisements, and narratives about ourselves that are more "truthy" than true. National myths can also be terribly dangerous: Hitler's ambitions were partly fueled by a story. But as Gottschall shows in this remarkable book, stories can also change the world for the better. Most successful stories are moral—they teach us how to live, whether explicitly or implicitly, and bind us together around common values. We know we are master shapers of story. The Storytelling Animal finally reveals how stories shape us.